Biomarkers of Response to Nintedanib in IPF - Vietri, Lucia; Reginato, Mariano; Gatti, Ilaria; dAlessandro, Miriana; Carnevale, Aldo; Papi, Alberto (Archives of Clinical and Biomedical Research, 2025)
IPF is an idiopathic, chronic and progressive interstitial pneumonia, in which there are currently none serum biomarkers with diagnostic and prognostic implications. However, they could become valuable tools to facilitate diagnosis, monitor disease progression and assess treatment efficacy. The pathogenesis of IPF involves repeated pulmonary damage on alveolar epithelial cells. Several studies have shown that in the bronchoalveolar lavage (BAL) of patients with IPF, eosinophilia greater than 10% is observed. Additionally, some studies have reported that nitric oxide (NO) plays a crucial role in the angiogenesis process in fibrotic lungs and upregulates the expression of Vascular Endothelial Growth Factor (VEGF). The aim of our study is to evaluate the role of blood eosinophil counts (BECs) and FeNO (fractional exhaled NO) as potential biomarkers for IPF. A total of 38 patients with IPF (mean age 75.5 ± 6.7 years) followed at the University of Ferrara-Italy was enrolled. We monitored BECs and FeNO at baseline (T0, time of diagnosis and initiation of antifibrotic therapy) and after 12 months (T12) of treatment. Patients with IPF undergoing therapy with Nintedanib exhibit, after one year of therapy, a higher BECs (0.54 ± 0.13 x10³/mcrl) compared to patients treated with Pirfenidone (0.13 ± 0.10 x10³/mcrl) or those not receiving antifibrotic treatment (0.02 ± 0.01 x10³/mcrl). Moreover, after one year of treatment, the FeNO concentration was also higher in patients on Nintedanib (29.42 ± 2.99 ppb) compared to those on Pirfenidone therapy (20.8 ± 20.5 ppb). BECs and FeNO are potential biomarkers of response to Nintedanib.